Development of STEAM-based JHS Mathematics Teaching Material to Enhance Students' Mathematical Connection - Akmal, Faisal Fazri; Asikin, Mohammad (Unnes Journal of Mathematics Education, 2022)
One of skills needed in the disruption era is the mathematical connection ability. However, this ability has not been optimally facilitated through learning process. In fact, the disruption era also encourages renewal, one of which is through the provision of quality learning resources both in terms of content and approach. In addition, the disrupstion era has also led to various approaches that more suitable with existing developments and changes, such as the STEAM approach. Therefore, it is important to develop a qualified STEAM-based mathematics teaching material to improve students' mathematical connection abilities. The development of this teaching material uses a modified Borg and Gall model of research and development (R&D) method. There are ten stages that aim to develop and describe the quality of STEAM-based mathematics teaching materials in three indicators, namely validity (characteristics suitability and feasibility), practicality (readability), and effectiveness in improving students' mathematical connection abilities. The final results are STEAM-based mathematics teaching materials that are valid (meet the teaching materials characteristics suitability and include in the very feasible category with feasibility score of 89,09%), practical (easy to understand with readability score of 67.13%), and effective in improving students’ mathematical connection abilities with moderate improvement category (with gain normalization index score of 0.395).